(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Natural catastrophes such as floods, cyclones and droughts strike West Bengal frequently each year. In addition, the lower Gangetic basin of Bengal has seen an increase in the frequency and severity of disasters as a result of climate change. The Sundarbans (South 24 Parganas district) and the areas nearby of West Bengal were hit hard by worst cyclones. The provision of water supply and sanitation services is the ultimate requirement for populations affected by disasters. The occurrence of natural disasters might potentially result in the emergence of epidemics such as cholera, diarrheal illnesses, dengue, malaria, and typhoid. By implementing deliberate disaster risk reduction measures on water supply, sanitation, and hygiene, the State Government and other stakeholders might potentially minimize the negative consequences of catastrophes. This paper reflects critical study and review of cyclones in Gangetic West Bengal during the period 2001-2020.